Nilai Etnopedagogi pada Novel Nu Ngageugeuh Legok Kiara Karya Dadan Sutisna - Eulis Entin; Usep Kuswari (JENTERA: Jurnal Kajian Sastra, 2024)
This research aims to elucidate the educational values of ethnopedagogy found in the novel Nu Ngageugeuh Legok Kiara by Dadan Sutisna. The approach used is descriptive, intending to detail the data, specifically related to the ethnopedagogical educational values in the novel. The research method employed is qualitative, which helps to describe the condition of the research subject and reveal the background of the research subject based on facts and reality. The data collected involves excerpts from the novel Nu Ngageugeuh Legok Kiara by Dadan Sutisna that reflect the introduction of local culture, traditional knowledge, engagement with nature, and appreciation of local wisdom. The stages of data collection involve reading, noting, and marking. The research results show that there are 41 data points of ethnopedagogical educational values, including 3 data points on the introduction of local culture, 8 data points on traditional knowledge, 10 data points on engagement with nature, and 20 data points on appreciation of local wisdom. The benefits of this research include strengthening the local cultural values contained in literature, assisting in the preservation of cultural heritage, and providing practical guidance in integrating local cultural elements into education to enhance the relevance and effectiveness of learning for students. AbstrakPenelitian ini bertujuan untuk menjelaskan kajian nilai pendidikan etnopedagogi yang terdapat dalam novel Nu Ngageugeuh Legok Kiara karya Dadan Sutisna. Pendekatan yang digunakan adalah deskriptif, yang bertujuan untuk menguraikan data, khususnya terkait nilai-nilai pendidikan etnopedagogi dalam novel. Metode penelitian yang digunakan adalah kualitatif, metode ini membantu menggambarkan kondisi subjek penelitian dan mengungkap latar belakang subjek penelitian berdasarkan fakta dan kenyataan. Data yang dikumpulkan melibatkan kutipan-kutipan dari novel Nu Ngageugeuh Legok Kiara karya Dadan Sutisna yang mencerminkan pengenalan budaya lokal, pengetahuan tradisional, keterlibatan dengan alam dan penghargaan terhadap kearifan lokal. Tahapan pengumpulan data melibatkan proses membaca, mencatat, dan menandai. Hasil penelitian menunjukkan bahwa terdapat 41 data nilai etnopedagogi, diantaranya 3 data pengenalan budaya lokal, 8 data pengetahuan tradisional, 10 data keterlibatan dengan alam, dan 20 data penghargaan terhadap kearifan lokal. Adapun manfaat  penelitian ini untuk memperkuat nilai-nilai budaya lokal yang terkandung dalam sastra, membantu pelestarian warisan budaya, serta memberikan panduan praktis dalam mengintegrasikan elemen budaya lokal ke dalam pendidikan untuk meningkatkan relevansi dan efektivitas pembelajaran bagi peserta didik.